Algorithm to predict dry-band arcing in fiber-optic cables. - Karady, G.G (IEEE Transactions on power delivery)
Utilities frequently use ADSS (all dielectric self-supporting) fiber-optic cables installed on transmission lines 3-6 m below the high voltage conductors. Dry-band arcing occurs on the fiber-optic cables when the cables are polluted and wet. This has been assumed to cause cable failures. An equivalent circuit has been developed to represent the polluted fiber-optic cable in the high voltage environment. The objective of this paper is to present a novel numerical method that can be used to predict dry-band arcing in fiber-optic cables. KCL (Kirchoff's current law) is used to derive node point equations for the equivalent circuit. Forward elimination and backward substitution of node voltage is used to solve the equations. The effect of pollution, tower arrangement, and conductor sag is analyzed. The numerical method has speed advantages over circuit simulation methods. This method includes conductor sag, nonuniform pollution, and variable capacitance. This algorithm can be used to predict dry band arcing in fiber-optic cables